Good practice policies to bridge the emissions gap in key countries. (March 2022) - Baptista, Luiz Bernardo; Schaeffer, Roberto; van Soest, Heleen L.; Fragkos, Panagiotis; Rochedo, Pedro R.R.; van Vuuren, Detlef; Dewi, Retno Gumilang; Iyer, Gokul; Jiang, Kejun; Kannavou, Maria; Macaluso, Nick; Oshiro, Ken; et al.
Highlights: Current national policies are not sufficient to meet the Paris Agreement goals. Collective increase in climate action is needed to stabilize warming at safe levels. Good practice policies can bridge the emissions gap to a below 2 °C world. These policies can create a bridge trajectory in key major-emitting countries. Abstract: One key aspect of the Paris Agreement is the goal to limit the global average temperature increase to well below 2 °C by the end of the century. To achieve the Paris Agreement goals, countries need to submit, and periodically update, their Nationally Determined Contributions (NDCs). Recent studies show that NDCs and currently implemented national policies are not sufficient to cover the ambition level of the temperature limit agreed upon in the Paris Agreement, meaning that we need to collectively increase climate action to stabilize global warming at levels considered safe. This paper explores the generalization of previously adopted good practice policies (GPPs) to bridge the emissions gap between current policies, NDCs ambitions and a well below 2 °C world, facilitating the creation of a bridge trajectory in key major-emitting countries. These GPPs are implemented in eleven well-established national Integrated Assessment Models (IAMs) for Australia, Brazil, Canada, China, European Union (EU), India, Indonesia, Japan, Russia, South Korea, and the United States, that provide least-cost, low-carbon scenarios up to 2050. Results show that GPPs can play an important role in each region, with energy supply policies appearing as one of the biggest contributors to the reduction of carbon emissions. However, GPPs by themselves are not enough to close the emission gap, and as such more will be needed in these economies to collectively increase climate action to stabilize global warming at levels considered safe.